Nanostructured forms of carbon deposit obtained during cracking of methane reaction over nanocrystalline iron catalysts - Kamila Maj; Ireneusz Kocemba (Adsorption Science & Technology)
During catalytic cracking of methane reaction, different carbon nanostructures can be formed. This paper shows the results of a characteristic nanostructured carbon deposit obtained during cracking of methane reaction over nanocrystalline iron catalysts with or without cobalt addition. The properties of the carbon deposit were determined by X-ray diffraction, scanning electron microscope with energy dispersive spectrometer equipment, thermogravimetry-differential thermal analysis coupled with mass spectrometry, time-of-flight secondary ion mass spectrometry analysis and surface area analysis (Brunauer-Emmett-Teller isotherm [BET]). Significant differences in the morphology and properties of the obtained carbon were found. The mechanism of the formation of carbon nanostructures for both iron catalysts is proposed.